Clinicopathologic, immunophenotypic, and molecular analysis of subcutaneous panniculitis‐like T‐cell lymphoma: A retrospective study in a tertiary care center. (20th November 2018) - Rutnin, Suthinee; Porntharukcharoen, Saneerat; Boonsakan, Paisarn
Abstract : Background: Subcutaneous panniculitis‐like T‐cell lymphoma (SPTL) as strictly defined by World Health Organization‐European Organization for Research and Treatment of Cancer classification is a rare cytotoxic α/β T‐cell lymphoma, characterized by primary involvement of subcutaneous tissue mimicking panniculitis. Objectives: To describe the clinicopathologic, immunophenotypic, and molecular features of SPTL. Methods: A 10‐year retrospective study of 18 patients diagnosed with SPTL was thoroughly reviewed according to clinicopathology, immunophenotype, and T‐cell receptor (TCR) gene rearrangement. Results: Of the 18 patients, 16 patients were definitely diagnosed with SPTL. The median age was 26 years (ranged 14‐53 years) with female predominance. Most patients presented with prolonged fever and subcutaneous nodules and/or plaques, usually located on lower extremities. 37.5% of patients had hemophagocytic syndrome. The main histopathology was lobular panniculitis with rimming of atypical lymphocytes highlighted by CD3+, CD8+, Beta‐F1+, granzyme B+, and Ki‐67 (50%‐90%). Monoclonal TCR gene rearrangement was found in 50% of patients and upper extremities involvement indicated a poor prognosis. Conclusion: The correlation between clinicopathologic and immunophenotypic study is the most helpful method to give a precise diagnosis of SPTL. Rimming of CD8+ atypical lymphocytes highlighted by high Ki‐67 index is highly specific for the diagnosis of SPTL.